BELAJAR JUJUR, BELAJAR MENGHITUNG: INOVASI PENDIDIKAN KARAKTER MELALUI KOPERASI KEJUJURAN NUMERASI - Rizki Diana; Nur Khasanah (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Character education at the primary school (SD) level plays an important role in building students' personalities, especially in instilling the value of honesty. In contrast, numeracy is one of the basic skills that students should have to support additional learning. The purpose of this study is to evaluate how effective the integration of honesty cooperative with numeracy learning is as an innovative method to teach character and improve elementary students' numeracy skills. The main problem encountered was the absence of a method that could combine moral values and academic skills simultaneously. This research used a qualitative-descriptive approach and conducted a case study of an elementary school that implemented an honesty cooperative. Data were collected over eight weeks through observation of cooperative activities, interviews with teachers and students, and documentation of transactions. The results showed that this model was able to increase student honesty by 85%, where students were more responsible in recording and paying for transactions. In addition, the numeracy test showed an increase in students' numeracy skills by 20-30%. Thus, the numeracy-based honesty cooperative is not only effective in shaping honest character but also in sharpening students' mathematical intelligence. This approach is relevant to be applied more widely in elementary schools.